A deusa compõe um “mito”: o jovem Odisseu em busca de veneno (Odisseia I, 255-68) (Nuntius Antiquus, 2010)
This paper explores the inter- and extradiegetical functions of a story about Odysseus narrated by Athena to Telemachos in Odyssey 1, 255-68. It is argued that the representation of Odysseus in search of poison for his arrows need not to be thought first and foremost as a non-Homeric element or a morally disturbing action, for it may be analyzed by means of epic themes (specially by the mêtis-megatheme) explored not only in the Odyssey but in the Iliad as well. Besides, this story anticipates and condenses the plot of the poem.